2006
DOI: 10.4049/jimmunol.176.2.974
|View full text |Cite
|
Sign up to set email alerts
|

OX40 Costimulation Synergizes with GM-CSF Whole-Cell Vaccination to Overcome Established CD8+ T Cell Tolerance to an Endogenous Tumor Antigen

Abstract: T cell costimulation via OX40 is known to increase CD4+ T cell expansion and effector function and enhances the development of T cell memory. OX40 costimulation can also prevent, and even reverse, CD4+ T cell anergy. However, the role of OX40 in CD8+ T cell function is less well defined, particularly in the setting of immune tolerance. To determine the effects of OX40 costimulation on the induction of the host CD8+ T cell repertoire to an endogenous tumor Ag, we examined the fate of CD8+ T cells specific for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 33 publications
(70 reference statements)
6
86
1
1
Order By: Relevance
“…This CTL activity is immunologically specific, in as much as none of these populations showed cytotoxic activities against the neu-negative CaD1 tumor cells. Similar degree of cytotoxicity was observed in the in vivo cytotoxicity assays, which is consistent with a report by Murata et al 45 that showed low to modest cytotoxicity activity in mice using this highly sensitive assay. More importantly, vaccination of DC neu cells stimulated significant anti-neu immunity in vivo, which protected all mice from challenge of Tg1-1 tumor cells expressing the rat neu Ag in wild-type FVB/N mice, whereas DNA vaccine only protected 50% of mice from Tg1-1 tumor cell challenge, indicating that DC neu vaccine induced much stronger neu-specific immunity than pcDNAneu DNA vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…This CTL activity is immunologically specific, in as much as none of these populations showed cytotoxic activities against the neu-negative CaD1 tumor cells. Similar degree of cytotoxicity was observed in the in vivo cytotoxicity assays, which is consistent with a report by Murata et al 45 that showed low to modest cytotoxicity activity in mice using this highly sensitive assay. More importantly, vaccination of DC neu cells stimulated significant anti-neu immunity in vivo, which protected all mice from challenge of Tg1-1 tumor cells expressing the rat neu Ag in wild-type FVB/N mice, whereas DNA vaccine only protected 50% of mice from Tg1-1 tumor cell challenge, indicating that DC neu vaccine induced much stronger neu-specific immunity than pcDNAneu DNA vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…17,[27][28][29][30][31][32] Conversely, amplified OX40 signaling can markedly enhance the protective immunity against infectious agents and tumors. 33 It is always believed that these findings are the sole costimulatory effects of OX40 to the T effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that OX40 signaling on Tregs leads to their functional inactivation without a reduction in their numbers suggests that OX40 could augment the antitumor immune effects of adoptive T cell therapy without inciting the replenishment of Tregs. OX40 costimulation enhances OX40-expressing CD8 + T cell function directly, as well as by means of CD4 + T cells (9). In the present experimental setting, in addition to the direct inhibition of Tregmediated suppression by OX40 costimulation, it is possible that OX40 signaling may have concomitantly increased a direct enhancement of adoptive CD8 + T cell function.…”
Section: Discussionmentioning
confidence: 77%
“…3T3 neu cells derived from NIH-3T3 cells overexpressing rat HER2/neu proto-oncogene were grown in 3T3 media with 0.3 μM methotrexate at 37˚C in 10% CO 2 . The 3T3 neu cells were genetically modified to express murine cytokine GM-CSF using retroviral vector MFG as previously described (9,16,17), resulting in a 3T3-neu/GM cell line.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation